2022
DOI: 10.1186/s12904-022-00926-3
|View full text |Cite
|
Sign up to set email alerts
|

General population-based study on preferences towards end-of-life care in Southern Thailand: a cross-sectional survey

Abstract: Background End-of-life care preferences are potentially due to individual choice and feature variation due to culture and beliefs. This study aims to examine end-of-life care preferences and any associated factors, among the general Thai population. This could inform physicians in regards to how to optimize the quality of life for patients that are near the end of their lives. Methods A cross-sectional study surveyed the general population in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…22,23 Multiple studies have evidenced that most patients with and without cancer do not prefer to die in hospital. 2427 This has been substantiated by a systematic review of 210 studies from 33 countries that demonstrated moderate evidence that the majority of individuals preferred to die at home 28 and a meta-analysis of three studies that demonstrated that a slight majority of patients without cancer preferred to die at home. 29 To our knowledge, no study has demonstrated a predominant preference for death in the acute care setting.…”
Section: Introductionmentioning
confidence: 95%
“…22,23 Multiple studies have evidenced that most patients with and without cancer do not prefer to die in hospital. 2427 This has been substantiated by a systematic review of 210 studies from 33 countries that demonstrated moderate evidence that the majority of individuals preferred to die at home 28 and a meta-analysis of three studies that demonstrated that a slight majority of patients without cancer preferred to die at home. 29 To our knowledge, no study has demonstrated a predominant preference for death in the acute care setting.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have shown that the home is the most frequently preferred place of end-of-life care (31-84%) among the general population [11][12][13][14][15][16]. These research results have had a stimulating effect on policies to promote home care.…”
Section: Introductionmentioning
confidence: 99%
“…The main priority at the end of life is to have a nice life and a good death. Patients' perceptions of the dignity and meaning of life can help them prepare for death [16]. Pitanupong et al (2021) found that cancer patients in end-of-life care wanted to receive the full truth about their disease rather than experience any distressing symptoms, were mentally aware in the last hour of life, felt meaningful in life, and could pass away with their loved ones around [17].…”
Section: Introductionmentioning
confidence: 99%